2002
DOI: 10.1046/j.1469-0705.2002.00642.x
|View full text |Cite
|
Sign up to set email alerts
|

Transient hydropic signs in the donor fetus after fetoscopic laser coagulation in severe twin–twin transfusion syndrome: incidence and clinical relevance

Abstract: Transient hydropic signs may develop in a proportion of donor fetuses after laser coagulation for severe twin-twin transfusion syndrome. This phenomenon is normally not associated with a poor prognosis, and possibly indicates an hemodynamic adaptation response following interruption of the transfusion process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 16 publications
5
41
1
1
Order By: Relevance
“…It has been shown that although the majority of cardiovascular perturbations will improve within days to weeks of therapy and ultimately resolve, 516 some will not and the hemodynamic condition of either fetus may suddenly worsen. 517,518 Therefore, although experience is thus far limited, fetal echocardiography for surviving twins should be considered at 24 to 48 hours after the procedure with additional follow-up dictated by clinical findings thereafter.…”
Section: Diagnosis and Hemodynamic Assessmentmentioning
confidence: 99%
“…It has been shown that although the majority of cardiovascular perturbations will improve within days to weeks of therapy and ultimately resolve, 516 some will not and the hemodynamic condition of either fetus may suddenly worsen. 517,518 Therefore, although experience is thus far limited, fetal echocardiography for surviving twins should be considered at 24 to 48 hours after the procedure with additional follow-up dictated by clinical findings thereafter.…”
Section: Diagnosis and Hemodynamic Assessmentmentioning
confidence: 99%
“…In 1999, Quintero et al [8] proposed a staging system that has been adopted by many [4,[9][10][11][12], sometimes with minor modifications [13,14]. According to this staging system (table 1), severe TTTS can be further characterized accord-Luks/Carr/Plevyak/Craigo/Athanassiou/ Ralston/Tracy Critically abnormal Doppler studies are defined as absent/ reversed end-diastolic velocity in the umbilical artery, reversal of flow in the ductus venosus, or pulsatile flow in the umbilical vein.…”
Section: Introductionmentioning
confidence: 99%
“…Occasionally, transient hydrops typically with small pleural effusion and slight skin edema could be seen in the donor few days after FLP (Figure 7). Gratacos and co-workers show 27% of donors after FLP developed one or more hydropic signs, and 90% of these were mild or moderate and transient (3-4 days); there was no intrauterine fetal demise of transient hydropic donor [31]. Transient hydrops may develop in a proportion of donor fetuses after FLP for severe TTTS, which is not associated with a poor prognosis.…”
Section: Ultrasound Findings After Fetoscopic Laser Photocoagulationmentioning
confidence: 90%